O crime de falso testemunho ou falsa perícia no Direito Penal brasileiro e comparado: o sujeito ativo e outras questões - Ana Luiza Almeida Ferro (2002)
Study about the crime of perjury/false testimony or false examination, including a historical view and emphasizing the question of the criminal and correlative themes in Brazilian and comparative criminal law, under the parameters of Brazilian law, doctrine and case law, as well as English, American, German, Norwegian, French, Italian, Portuguese, Spanish, Argentinean, Chilean and Cuban law. Initially, it focus the testimonial and expert evidence, giving special attention to the first, which is analyzed in its juridical and psychological aspects. In the nuclear part, considered the alterations in articles 342 and 343 of the Penal Code provided by Act no.10268, 08.28.2001, it studies the theme of the criminal, in a critical and eventually propositional way, through its various currents and controversies, examining the situations of the accused, the defendant and the privilege against self-incrimination, the victim, the witness who does not state on oath and the one who is not warned to tell the truth, the litigant in civil procedure who gives testimony in court, the expert and the assistant expert, the accountant, as well as the possibility of conspiracy, aiding and abetting, laying stress upon the abetting committed by the defendant favored by the falsehood, the aiding and abetting imputed to the lawyer and the incidence of aiding or abetting when the author of the falsehood is not subject to imputability. Finally, it considers the treatment of the matter by some foreign laws and codes, recent or old, having a democratic or authoritarian approach, belonging to the systems of civil law, common law or socialist law, and selected because of their importance or for representing a specific juridical and ideological tendency.